Shop Around and You Pay More - Ji Yan; Kun Tian; Huw D. Dixon; Saeed Heravi; Peter Morgan (Center for Economic Studies and ifo Institute (CESifo), 2014)
We examine the relationship between the prices paid by households and their shopping patterns measured in terms of shopping frequency and the range of stores visited. We use the TNS data which allows us to control for household heterogeneity. The main contribution of the paper is that we find proper instruments to correct for endogeneity of shopping patterns. And we find that there exists a robust positive relationship between the price paid and the number of store visited. We argue that visiting larger number of stores makes households less likely to save using store-loyalty discounts.
Keywords: D03; D12; D83; M31; 330; shopping frequency; price; store loyalty; demographics